EuroGOOS roadmap for operational coastal downstream services - Ghada El Serafy; Lőrinc Mészáros; Vicente Fernández; Arthur Capet; Jun She; Marcos Garcia Sotillo; Angelique Melet; Sebastien Legrand; Baptiste Mourre; Francisco Campuzano; Ivan Federico; Antonio Guarnieri; et al. (Frontiers in Marine Science, 2023)
The EuroGOOS Coastal working group examines the entire coastal value chain from coastal observations to services for coastal users. The main objective of the working group is to review the status quo, identify gaps and future steps needed to secure and improve the sustainability of the European coastal service provision. Within this framework, our white paper defines a EuroGOOS roadmap for sustained “community coastal downstream service” provision, provided by a broad EuroGOOS community with focus on the national and local scale services. After defining the coastal services in this context, we describe the main components of coastal service provision and explore community benefits and requirements through sectoral examples (aquaculture, coastal tourism, renewable energy, port, cross-sectoral) together with the main challenges and barriers to user uptake. Technology integration challenges are outlined with respect to multiparameter observations, multi-platform observations, the land-coast-ocean continuum, and multidisciplinary data integration. Finally, the technological, financial, and institutional sustainability of coastal observing and coastal service provision are discussed. The paper gives special attention to the delineation of upstream and downstream services, public-private partnerships and the important role of Copernicus in better covering the coastal zone. Therefore, our white paper is a policy and practice review providing a comprehensive overview, in-depth discussion and actionable recommendations (according to key short-term or medium-term priorities) on the envisaged elements of a roadmap for sustained coastal service provision. EuroGOOS, as an entity that unites European national operational oceanography centres, research institutes and scientists across various domains within the broader field of operational oceanography, offers to be the engine and intermediary for the knowledge transfer and communication of experiences, best practices and information, not only amongst its members, but also amongst the different (research) infrastructures, institutes and agencies that have interests in coastal oceanography in Europe.

Uncertainty estimation for operational ocean forecast products—a multi-model ensemble for the North Sea and the Baltic Sea - Inga Golbeck; Xin Li; Frank Janssen; Thorger Brüning; Jacob W. Nielsen; Vibeke Huess; Johan Söderkvist; Bjarne Büchmann; Simo-Matti Siiriä; Olga Vähä-Piikkiö; Bruce Hackett; Nils M. Kristensen; et al. (Ocean Dynamics, 2015)

High pressure disruption: a two-step treatment for selective extraction of intracellular components from the microalga Porphyridium cruentum - Sebastien Jubeau; Luc Marchal; Jeremy Pruvost; Pascal Jaouen; Jack Legrand; Joel Fleurence (Journal of Applied Phycology, 2013)